2020
DOI: 10.1111/jvim.15881
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of recurrent seizure disorders and epilepsy in cats under primary veterinary care in the United Kingdom

Abstract: Background: Little epidemiological evaluation of recurrent seizure disorders in cats currently exists in veterinary literature. Objectives: To report the prevalence and risk factors for recurrent seizure disorders (RSD) and epilepsy in cats presented to primary care veterinary practices in the United Kingdom (UK). Animals: A total of 285 547 cats under veterinary care during 2013 presenting to 282 primary care clinics in the UK. Methods: Cohort study using multivariable logistic regression modeling for risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…First, dogs referred for further investigation of epileptic seizures may have more refractory disease proving more difficult to control in the primary care setting; secondly, the time and expertise available for the management of chronic conditions such as epilepsy in referral practice does not reflect that in general practice. Studies that have utilised health records from primary-care veterinary practices have mainly evaluated the prevalence and risk factors of epileptic seizures in both dogs and cats (Erlen et al 2018, O'Neill et al 2020. Less emphasis has been placed on the clinical approach to epileptic seizures by primary care clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…First, dogs referred for further investigation of epileptic seizures may have more refractory disease proving more difficult to control in the primary care setting; secondly, the time and expertise available for the management of chronic conditions such as epilepsy in referral practice does not reflect that in general practice. Studies that have utilised health records from primary-care veterinary practices have mainly evaluated the prevalence and risk factors of epileptic seizures in both dogs and cats (Erlen et al 2018, O'Neill et al 2020. Less emphasis has been placed on the clinical approach to epileptic seizures by primary care clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24]26,27 A 2020 study by O'Neill et al found that 0.15% of BSH cats and 0.16% of the total number of cats presenting to primary veterinary care over 1 year showed recurrent epileptic seizures and no convincing evidence for a high prevalence of recurrent epileptic seizures in any cat breed, but the small number of purebred cats with epilepsy might have influenced their results. 25 Although not an aim of this study, pedigree data available through SVERAK confirmed that two cats in the PIE group were closely related; both had generalised epileptic seizures. Further studies, including pedigree data with a larger number of affected cases, are needed to evaluate genetic epilepsy in cats.…”
Section: Discussionmentioning
confidence: 59%
“…Given the large area of forebrain affected in this case, it seems surprising that the clinical response to anti‐seizure medication was so positive. Observation of feline seizures by owners may be poor compared to that of dogs 40,41 ; however, this is less likely to be a significant feature in this case as the cat was indoor only. The good response in this case supports the possible benefits of pursuing treatment despite severe imaging changes in similar patients.…”
Section: Discussionmentioning
confidence: 79%